Clinical features of depression in Asia: Results of a large prospective, cross-sectional study - Manit Srisurapanont (2018)
Introduction: The objective of this study was to investigate the clinical features of depression in Asian patients. Methods: It was a cross-sectional, observational study of depression in China, Korea, Malaysia, Singapore, Taiwan, and Thailand. Participants were drug-free outpatients with depressed mood and/or anhedonia. Symptoms and clinical features were assessed using the Montgomery-Asberg Depression Rating Scale, Symptoms Checklist 90-Revised (SCL-90-R), and the Fatigue Severity Scale. Other measures included the Medical Outcome Survey 36-Item Short-Form Health Survey (SF-36), the Sheehan Disability Scale, and the Multidimensional Scale of Perceived Social Support (MSPSS). Results: A total of 547 outpatients with major depressive disorder were included in the analyses. Among the Montgomery-Asberg Depression Rating Scale symptoms, "reported sadness" and "reduced sleep" had the highest severity, with means (SDs) of 3.4 (1.2) and 3.4 (1.6), respectively. Apart from the SCL-90-R depression and anxiety domains, the SCL-90-R obsession-compulsion syndrome had the highest domain score, with a mean (SD) of 1.9 (0.9). Among eight domains, the mean (SD) SF-36 pain subscale score of 58.4 (27.7) was only second to that for the SF-36 physical function. In comparison to other disability domains, the Sheehan Disability Scale work/school had the highest subscale score, with a mean (SD) of 6.5 (2.9). The mean (SD) MSPSS "family" subscale score of 4.7 (1.7) was higher than the MSPSS "friends" and "significant others" subscale scores. Discussion: This study suggests that pain has a minimal impact on the quality of life in Asian patients with depression. Noteworthy issues in this population may include insomnia, obsessive-compulsive symptoms, working/school disability, and family support. © 2013 Wiley Publishing Asia Pty Ltd.